/

In a study of the average weight of babies at different time intervals after birth, the babies’ measured weight is which of the following variables?

A. Independent

B. Control

C. Dependent

D. Constant

Answer Explanation:

In this case, we are measuring average weight of the babies with time. The weight of the babies will vary with time, meaning when we vary time, the average weight of the babies will be different. Here, time is independent while average weight is dependent variable.

Therefore, the Correct Answer is C.

More Questions on TEAS 7 Math

  • Q #1: A homeowner has hired two people to mow his lawn. If person A is able to mow the lawn in 2 hr by herself and person B is able to mow in lawn in 3 hr by himself. Which of the following is the amount of time it would take for both person A and B to mow the lawn together?

    A. 5 hours

    B. 2.5 hours

    C. 1.2 hours

    D. 1 hours

    Answer Explanation

    We know that the two people work on the same work but the time to complete the work differs. Thus, the rate of doing the work for each person is as follows:

    Rate of work for person A = 1 /2 work per hr

    Rate of work for person B=1/3 work per hour

    If person A and B work together, the time of doing the same work will be less than the fastest person A. Thus, we combine the two rates of A and B

    We have 1 work and time to complete by both A and B becomes

  • Q #2: What is the least common denominator for the fractions below? (Round the answer to the nearest integer) 1/2, 2/3, 4/5

    A. 30

    B. 25

    C. 7

    D. 19

    Answer Explanation

    We determine least common denominator (LCD) using prime factorization of denominators as follows

    2=1*2

    3=1*3

    5=1*5

    Thus, LCD of 2, 3, 5 = 2*3*5=30

  • Q #3: (x/y)-z=rw Solve for x in the equation above.

    A. X=y(z+rw)

    B. X=rw(y-z)

    C. X=rwy+z

    D. X=rwy-z

    Answer Explanation

    Given the equation (x/y)-z=rw, we make x the subject of the formula as follows:

    (x/y)-z=rw

    Add z to both sides of the equation

    (x/y)-z+z=rw+z

    (x/y)=rw+z

    Multiply both sides by y

    (x/y)*y=y(rw+z)

    X=y(rw+z)

    Rearranging the equation results in:

    X = y(z+rw)